Analisis Challenge Stress dan Hindrance Stress Terhadap Kepuasan Kerja dan Kinerja Pegawai Pada Masa Pandemi Covid-19 - Irianti, Nuvaria; Gunarto, Muji; Istianda, Meita (Jurnal Manajemen, 2023)
This article aims to determine the type of stress experienced by employees during the Covid-19 pandemic. Each employee is given a target that must be achieved, while during the Pandemic economic growth is not good. Seeing this phenomenon, there appears a type of stress that can have a positive effect (challage stressor) and a negative effect (hindrance stressor) on employee performance and satisfaction. The methodology used is a quantitative method approach, with a total sample of 350 respondents spread across the island of Sumatra. This research shows that not all stress has a bad impact, but good types of stress are used as opportunities to grow, develop and become triggers to meet targets so as to provide performance and satisfaction. On the other hand, if the stress that arises is used as a burden so that the target is not achieved, and has an impact on low performance and employee satisfaction.